Nickel nanoparticles set a new record of strength - A. Sharma (Nature Portfolio, 2018)
While metallic nanosized objects are stronger than their macroscopic counterparts, they rarely reach the metal’s maximum theoretical strength. Here, the authors produce faceted nickel nanoparticles and show that their strength under compression matches the theoretically predicted strength in the literature.